아시아국가 스마트시티 구축사업에 대한 ‘저개발의 개발’론적 고찰 - 김기홍(Kim, Ki Hong) (문화콘텐츠연구, 2020)
본 논문은 영국 문화연구의 대표적 학자인 레이먼드 윌리엄즈와 종속이론가 안드레 프랑크의 이론을 바탕으로, 전 세계적으로 진행 중인 스마트시티 구축사업을비판적으로 연구한 것이다. 스마트시티는 첨단 기술을 이용해 환경폐기물을 줄이고 시민 삶의 질을 제고하는 혁신적인 도시 전략으로서, ‘ICT 기술’, ‘도시경영’, ‘환경’, ‘경제발전’, ‘민주주의’ 등이 핵심 요소다. 선진국은 도시 구성원의 삶의 질 향상과 지속 가능한 환경 관리 체제 구축에 관심을 두고 있다. 첨단 기술은 물론, 기본적인 인프라조차 부족한 저개발 및 개발도상 국가는 스마트시티 구축사업을 통해국가의 발전을 혁신적으로 향상시키고자 한다. 아세안의 경우, 10개국으로 구성된아세안 스마트시티 네트워크를 통해 서로 협력하며 26개 시범도시를 선정하고 지원해, 이들 거점 도시들을 바탕으로 지역 전체의 총체적인 질적 전환을 꾀하고 있다. 다수의 아프리카 국가들 역시 대규모 도시 개발 사업을 전개하고 있다. 실현과성공의 가능성 문제가 제기된다. 글로벌 차원의 대도시 개발 사업은 제국주의의 식민지배 함의와 자본주의 비판 분야에서 오랜 검토대상이었다. 특히 프랑크의 ‘저개발의 개발’ 이론에 의하면, 중심부의 선진화된 지역은 주변부의 저개발에 기대어발전을 유지하므로, 배후지는 낙수효과를 기대할 수 없고 오히려 지속적 수탈의 대상이 된다. 연구 결과, 종속이론의 주장에 부합하는 우려할만한 ‘저개발의 개발’적사태가 벌어지고 있었다. 저개발 국가의 스마트시티 구축사업에 대한 본연적인 재고가 필요한 시점이다. The Smart City creation projects are underway all around the world. It is an innovative urban strategy that uses advanced technology to reduce environmental waste and improve the quality of citizens’ lives, with key elements such as “ICT technology,” “urban management,” “environment,” “economic development” and “democracy.” Advanced countries are interested in improving the quality of life for urban residents and establishing a sustainable environment management system. Underdeveloped and developing countries, which lack not only cutting-edge technology but also basic infrastructure, want to revolutionary advance the development of lagging regions and countries through the smart city creation projects. In this regards, ASEAN Smart City Network the organization of 10 ASEAN city members was organized and has been selected and supported 26 pilot cities, seeking a holistic and qualitative transformation of the entire region based on these hub cities. Many countries in Africa are also working on large-scale metropolis projects for national development. The question of feasibility and success remains. The development project of Metropolis at the global level has long been a subject of consideration in the implications of imperialism's colonial rule and the issue of criticism of capitalism. In particular, according to Andre G. Frank's theory of “development of underdevelopment,” advanced areas in the center are parasitical on the underdevelopment of the hinterland, so diffusionists’ idea of a trickle-down effect cannot be expected, rather is subject to continued exploitation. Studies have shown that there was a worrisome ‘development of underdevelopment’ phenomena that matched the arguments of dependence theory. It is time to reconsider the smart city construction project of underdeveloped countries. KCI Citation Count: 2